The Influence Of Work Environment And Work Discipline On Employee Productivity At Hasgradini Cibeureum Tasikmalaya Convection - Alyanti, Tati; Sutrisna , Arga; Asyiah , Ai Kusmiati (Journal of Management, Economic, and Accounting, 2023)
This study aims to determine the effect of work environment and work discipline on employee productivity at the Hasgradini Cibeureum Tasikmalaya Convection. The method used in this study is a quantitative approach with a sample of 50 respondents from Hasgradini Cibeureum Tasikmalaya employees. The data used in this study are primary data and secondary data which are then processed using the Mendeley application. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. The results show that simultaneously the work environment and work discipline have a significant effect on employee productivity. Partially, the work environment has a significant effect on employee productivity. Exactly work discipline has a significant effect on employee work productivity.